Neuronal nitric oxide synthase : a biomarker for Alzheimers disease : interaction of neuronal nitric oxide synthase with beta-amyloid peptides in the brain - Padayachee, Eden Rebecca (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
High levels of the amino acid arginine and low levels of the product citrulline in the cerebrospinal fluid of Alzheimer's patients could mean that there is a decrease in the enzymes that metabolize this amino acid. One such enzyme is neuronal nitric oxide synthase (nNOS). In this study, neuronal nitric oxide synthase (nNOS), sourced from bovine brain was extracted and concentrated using two methods of precipitation: poly (ethylene glycol) 20 000 (PEG) and ammonium sulphate [(NHâ‚„)â‚‚S0â‚„). These two techniques gave no increase in yield nor fold purification and hence were abandoned in favour of ion exchange chromatography by DEAE-Sepharose. The enzyme was then successfully purified by anion-exchange and after dialysis produced a 38% yield and three fold purification and yielded the highest specific activity of 2.27 U/mg. Neuronal nitric oxide synthase (nNOS) was a heterodimeric protein with a total molecular mass of Â± 225 kDa (95 and 130 kDa monomers). The temperature and pH optima of the enzyme were 40â °C and 6.5, respectively. The kinetic parameters (KM and Vmax) of nNOS were 70 Î¼M and 0.332 Î¼mol.minâ »Â¹, respectively. Moreover neuronal nitric oxide synthase (nNOS) was relatively stable at 40â °C (tÂ½ = 3 h). It was also confirmed that Î²-amyloid peptides inhibited nNOS when bound to the enzyme and that nNOS behaved as a catalyst in fibril formation through association-dissociation between enzyme and Î²-amyloid peptide. It was further shown that AÎ²â‚ â‚‡â‚‹â‚‚â‚ˆ inhibited nNOS the most with a Ki of 1.92 Î¼M and also had the highest Stern-Volmer value (Ksv) of 0.11 Î¼Mâ »Â¹ indicating tight binding affinity to nNOS and easier accessibility to fluor molecules during binding. Congo red, turbidity, thioflavin-T assays and transmission electron microscopy were successfully used to detect and visualize the presence of fibrils by studying the process of fibrillogenesis. Computerized molecular modeling successfully studied protein dynamics and conformational changes of nNOS. These results correlated with resonance energy transfer (FRET) results which revealed the distance of tryptophan residues from the arginine bound at enzyme active site. Both the aforementioned techniques revealed that in the natural state of the enzyme with arginine bound at the active site, the tryptophan residues (TRPâ‚†â‚‚â‚… and TRPâ‚‡â‚‚â‚ ) were positioned at the surface of the enzyme 28 Ã… away from the active site. When the amyloid peptide (AÎ²â‚ â‚‡â‚‹â‚‚â‚ˆ) was bound to the active site, these same two amino acids moved 14 Ã… closer to the active site. A five residue hydrophobic fragment AÎ²â‚ â‚‡â‚‹â‚‚â‚ [Leuâ‚ â‚‡ - Valâ‚ â‚ˆ - Pheâ‚ â‚‰ - Pheâ‚‚â‚€ - Alaâ‚ ] within AÎ²â‚ â‚‡â‚‹â‚‚â‚ˆ was shown by computer modeling to be critical to the binding of the peptide to the active site of nNOS.
Keywords: Alzheimer's disease; Nitric-oxide synthase; Biochemical markers; Amyloid beta-protein; Peptide hormones